Adaptive livelihood strategies among small-scale fishing households to climate change-related stressors in Central Coast Vietnam - Phuong T.A. Huynh; Ngoan D. Le; Sen T.H. Le; Thang N. Tran (International Journal of Climate Change Strategies and Management, 2021)
Purpose – This paper aims to examine adaptive livelihood strategies used by small-scale fishing households in the two coastal communities in Central Vietnam under the context of climate change-related stressors. Design/methodology/approach – Field data were collected through mixed quantitative and qualitative methods including a review of secondary data, key-informant interviews, group discussions and household surveys with 300 sampled fishing households. The qualitative data support the analysis and discussion of quantitative data. Findings – The results showed local households’ perception of the presence and influence of multiple non-climate and climate stressors on their fishery-based livelihoods in terms of employment and income in many ways. The affected households exerted to develop a diversity of adaptation methods within and out of fishing to sustain their livelihoods and cover a deficit in household income. The household socio-demographic characteristics particularly education, labour force, fishing equipment and social support played significant importance in characterising the categories of adaptation strategies among the survey households. The role of local governments in creating an enabling environment for local-level adaptation, as well as protecting marine and coastal ecosystems was rather limited despite their recognized importance. Originality/value – The paper provides an empirical case of how small-scale fishing households in coastal communities in Central Vietnam are adapting to climate-related stressors. It suggests policy should promote livelihood diversification opportunities and address household-level constraints for adaptation. Fisheries management plan is urgently needed to control illegal fishing activities for sustainable use of coastal and marine fishery resources and the appropriate mechanism is important to stretch local governments’ resources for better supporting local-level adaptation.